Cartografias de São Paulo: imagens e subjetivações da cidade a partir da mobilidade urbana - Borges, Christina Maria de Marchiori (2019)
This thesis investigates the perception of users about urban images and the subjectivity aroused in users of the 408 A-10 Machado de Assis - Cardoso de Almeida bus line, in the city of São Paulo. Besides the images, we investigate in wich way the spaces are extent, many of them of historical and tourist nature, are known and appropriated by the users. Based on some concepts of the thinking of Gilles Deleuze and Félix Guattari, we find the directions of the subjectivity agitations of the images: if in the direction of machinic assemblages influenced by the Capital's logic or in the direction of alternative assemblages, with schizos and traits that indicate and openings to other individual and collective subjectivities not programmed by dominant thinking. We also investigate the complex intersections between look, images and landscapes in the city